Analysis of Sociomathematical Norms Aspect Based on Mathematical Reflective Thinking Ability - Diah Sofiana Eka Putri Siregar; Hikmatul Khusna (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
In Learning mathematics, sociomathematical norms are needed. Sociomathematical norms are rules set during mathematics learning regarding truth, cooperation, freedom of opinion, and responsibility. This study aims to determine aspects of sociomathematical norms based on the mathematical reflective thinking ability of class VIII students at SMPN 12 Bekasi. This research uses a descriptive method with a qualitative approach. The instruments used in this study used questions, questionnaires, interviews, and observations. The selected respondents were 3 respondents with high, medium, and low category mathematical reflective thinking abilities. The data validity technique in this study uses triangulation of methods, namely questionnaires, interviews, and observations. The conclusion of this study found that respondent R1 with high mathematical reflective thinking ability has a high sociomathematical norms aspect, R2 with medium mathematical reflective thinking ability has a medium sociomathematical norms aspect, R3 with low mathematical reflective thinking ability has a low sociomathematical norms aspect. Researchers suggest that further research can be conducted at different levels of education so that it can discuss more broadly the aspects of sociomathematical norms that students have.